The Relationship between Interest Rate, Exchange Rate and Stock Price: A Wavelet Analysis - Mohamed Essaied Hamrita; Abdelkader Trifi (International Journal of Economics and Financial Issues, 2011)
This paper examines the multi-scale relationship between the interest rate, exchange rate and stock price using a wavelet transform. In particular, we apply the maximum overlap discrete wavelet transform (MODWT) to the interest rate, exchange rate and stock price in US over the period from january 1990 to december 2008 and using the definitions of wavelet variance, wavelet correlation and cross-correlations to analyze the association as well as the lead/lag relationship between these series at the different time scales. Our results show that the relationship between interest rate and exchange rate is not significantly different from zero at all scales. On the other hand, the relationship between interest rate returns and stock index returns is significantly different from zero only at the highest scales. The exchange rate returns and stock index returns have a bidirectional relationship in this period at longer horizons.